Extremal Unicyclic Graphs with Respect to Vertex–Degree–Based Topological Indices (2022)
In this paper we present a general criteria to decide when the cycle Cn on n vertices and Hn,1, the coalescence of the star Sn−2 with the cycle C3, are extremal unicyclic graphs of a vertex-degree-based (VDB) topological index. We show that many of the well known results on extremal values of VDB topological indices over unicyclic graphs can be obtained as particular cases of ours. Moreover, we obtain new results on extremal values of VDB topological indices, such as the generalized Geometric-Arithmetic indices, the generalized Atom-Bond-Connectivity indices, and its exponentials, among others.